1995
DOI: 10.1002/j.1460-2075.1995.tb07136.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MHC class I expression due to interference with p105-NF kappa B1 processing by Ad12E1A.

Abstract: We have previously demonstrated that expression of major histocompatibility complex (MHC) class I genes is repressed in baby rat kidney cells transformed by early region 1 of oncogenic adenovirus type 12 (Ad12E1). Reduced expression of MHC class I antigens contributes to the escape of Ad12‐transformed cells from T‐cell‐mediated immune surveillance and to tumour induction. In this study, we show that repression of MHC class I expression by Ad12E1A is mediated via the H2TF1 element of the MHC class I promoter. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 65 publications
4
28
2
Order By: Relevance
“…The biological role of p50 homodimers appears to be ambiguous. In some experimental systems p50/p50 homodimers activated transcription from promoters with speci®c kB sites (Collart et al, 1990;Fujita et al, 1992Fujita et al, , 1993Kretzschmar et al, 1992;Schouten et al, 1995;Ten et al, 1992). In other experimental systems these homodimers were unable to activate gene transcription (Beg et al, 1992;Franzoso et al, 1992;Kang et al, 1992;Plaksin et al, 1993;Schmitz and Baeuerle, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological role of p50 homodimers appears to be ambiguous. In some experimental systems p50/p50 homodimers activated transcription from promoters with speci®c kB sites (Collart et al, 1990;Fujita et al, 1992Fujita et al, , 1993Kretzschmar et al, 1992;Schouten et al, 1995;Ten et al, 1992). In other experimental systems these homodimers were unable to activate gene transcription (Beg et al, 1992;Franzoso et al, 1992;Kang et al, 1992;Plaksin et al, 1993;Schmitz and Baeuerle, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Among genes positively regulated by p50/p50 homodimers are TNF-alpha, major histocompatibility complex (MHC) class I genes, as well as its own gene nf-kb1 which encodes p50 as well as the inhibitor protein p105 (Collart et al, 1990;Schouten et al, 1995;Ten et al, 1992). There are also data indicating that p50/p50 binds with high a nity to certain kB sites in the promoter region of ikb-a and nf-kb2 genes (Le Bail et al, 1993;Liptay et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports showed that p50 homodimers have the capacity to activate in vivo and in vitro a promoter containing B sites (22,23,31). Moreover, other studies have postulated that the p50 homodimers are involved in regulating the expression of tumor necrosis factor alpha, NF-B1 (p105), and major histocompatibility complex (MHC) class I genes (17,51,55,61), although the surface expression levels of MHC class I molecules in cells of p50 null mice are normal (53). Previous in vitro studies and transient-transfection experiments have shown that Bcl-3 is able to remove p50 homodimers from DNA, thus allowing transcriptional activation to occur through the potent p50-RelA heterodimers (20,21,26,27,34,42,43,64).…”
mentioning
confidence: 99%
“…Therefore, an upstream oligo, U1, corresponding to the RT1.A l sequence, and a downstream oligo, D1, derived from RT16 (24), were used for RT-PCR of total RNA from the Ad5-transformed BRK cell line BXc22, which expresses high levels of RT1-A u (see Fig. 1B) (25). The PCR product of 473 bp was subcloned in the AT vector pCR2.1 (Invitrogen), resulting in PCR2.1-RT1-A u 5Ј.…”
Section: Methodsmentioning
confidence: 99%